The effects of in-hospital deprescribing on potential prescribing omission in hospitalized elderly patients with polypharmacy - Miho Kaminaga (Nature Portfolio, 2021)
Abstract No studies to investigate the effect of a deprescribing intervention on the occurrence of potential prescribing omissions (PPOs) among elderly patients with polypharmacy have been conducted. Therefore, the effect of deprescribing on PPOs among elderly patients with polypharmacy was investigated. All 121 consecutive elderly patients who received in-hospital deprescribing interventions were evaluated. The primary outcome was any occurrence of PPOs based on the 2015 STOPP/START criteria. The proportion of patients who had any PPOs significantly increased after the deprescribing interventions (52.9% vs 77.7%, p < 0.001). In the multivariable analysis, older age was the only independent risk factor associated with an increased risk of any PPOs after the deprescribing interventions (OR 1.08, 95% CI 1.01 to 1.16). In-hospital deprescribing interventions for elderly patients with polypharmacy may increase the occurrence of PPOs. Further study is warranted to investigate the effects on clinical outcomes of the increased occurrence of PPOs due to the deprescribing intervention.